PENGARUH OPINI AUDIT DAN REPUTASI KAP PADA AUDITOR SWITCHING DENGAN FINANCIAL DISTRESS SEBAGAI VARIABEL MODERASI - Putra, I Gusti Bagus Bayu Pratama; Suryanawa, I Ketut (E-Jurnal Akuntansi; Vol 14 No 2 (2016), 2016)
In maintaining the reliability of a company's financial statements and auditor's independence, the companies are required to conduct an audit or rotation. The government has set obligations of auditor rotation with the issuance of the Decree of the Minister of Finance of the Republic of Indonesia No. 359 / KMK.06 / 2003 article 2 of " Jasa Akuntan Publik " (amendments to the Decree of the Minister of Finance No. 423 / KMK.06 / 2002). The regulation was later updated with the enactment of the Minister of Finance of the Republic of Indonesia Number 17 / PMK.01 / 2008 on " Jasa Akuntan Publik ". Regulations on auditor rotation, will cause the compan ies to perform the auditor switching . In this study, the sample used are companies that listed on the Indonesian Stock Exchange from 2011 to 2013. Analysis data that used is Moderated Regression Analysis test (MRA). The results showed the influence of audit opinion on auditor switching but, the firm's reputation variable has no influence on the auditor switching, and moderation variable financial distress is not able to strengthen or weaken the effect of audit opinion and the firm ’s reputation on the auditor switching.
Keywords: opini audit; reputasi KAP; financial distress; auditor switching